2014
DOI: 10.2139/ssrn.2529168
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Updating: Evidence from a Brazilian Nowcasting Model

Abstract: How often should we update predictions for economic activity? Gross domestic product is a quarterly variable disseminated usually a couple of months after the end of the quarter, but many other macroeconomic indicators are released with a higher frequency, and financial markets react very strongly to them. However, most of the professional forecasters, including the IMF, the OECD, and most central banks, tend to update their forecasts of economic activity only two to four times a year. The main exception is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 0 publications
3
20
0
Order By: Relevance
“…The statistical significance of the reduction in RMSE is highlighted with asterisks. This would imply that the strategy of exploiting the newsflow in real time is clearly better than waiting for the last data release of each block before updating the model, in line with the conclusion reached by Bragoli et al (2015). Visually, this is most clear for news blocks 4 and 6 in Figure 4, containing releases for industrial production, sales, factory orders, consumer spending and the Sentix index.…”
Section: Model Selectionsupporting
confidence: 60%
See 2 more Smart Citations
“…The statistical significance of the reduction in RMSE is highlighted with asterisks. This would imply that the strategy of exploiting the newsflow in real time is clearly better than waiting for the last data release of each block before updating the model, in line with the conclusion reached by Bragoli et al (2015). Visually, this is most clear for news blocks 4 and 6 in Figure 4, containing releases for industrial production, sales, factory orders, consumer spending and the Sentix index.…”
Section: Model Selectionsupporting
confidence: 60%
“…The second element of the gain shown in expression 4, which we relate to quality, can be expanded as follows 8 :…”
Section: The Kalman Filter Gainmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have also found that bridge equations with factors have better forecasting performance than forecast averages of bridge equations with separate explanatory variables. Bragoli et al (2014) incorporate daily data releases from various sources to update nowcasts of Brazil's GDP, a noteworthy approach.…”
Section: Literature Overviewmentioning
confidence: 99%
“…However, Statistics Canada, differently from other countries, also publishes a monthly figure together with quarterly GDP growth eight weeks after the end of the reference period (the monthly real GDP relative to January is available only in March; the quarterly real GDP relative to Q1 is available only in May). Moreover, compared with other countries, Canada lacks some important series linked to production-namely industrial production and capacity utilization-that have been proved to be important in tracking real GDP growth for other economies given their timeliness 1 The United States (Lahiri and Monokroussos, 2013), the euro area (Angelini et al, 2010;Angelini et al, 2011;and Camacho and Perez-Quiros, 2010), France (Barhoumi et al, 2010), Ireland (D'Agostino et al, 2008and Liebermann, 2012), the Netherlands (De Winter, 2011), the Czech Republic (Arnostova et al, 2011;and Rusnák, 2013), New Zealand (Matheson, 2010), Norway (Aastveit et al, 2012;and Luciani and Ricci, 2014), Switzerland (Siliverstovs, 2012), China (Yiu andChow, 2010), Turkey (Modugno et al, 2016), Brazil (Bragoli et al, 2015), Mexico (Caruso, 2015), and Indonesia (Luciani et al, 2015). Moreover, the same framework has been applied to nowcast other variables than real GDP; see, among others D' Agostino et al (2015) for the euro area trade variables and Modugno (2013) for U.S. inflation.…”
mentioning
confidence: 99%